Temporary Clipping of the Intracavernous Internal Carotid Artery: A Novel Technique for Proximal Control. Issue 2 (11th December 2020) - Basma, Jaafar; Krisht, Khaled M; Lee, Paul; Cai, Li; Krisht, Ali F
Abstract: BACKGROUND: Securing proximal control in complex paraclinoid aneurysm surgery through traditional techniques may be challenging and risky in certain situations. Advancements of anatomical knowledge of the cavernous sinus (CS) and hemostasis have made it more accessible as a surgical option. OBJECTIVE: To describe the technique of temporary clipping of the horizontal segment of the intracavernous internal carotid artery (IC-ICA) in preparation for permanent clipping of complex paraclinoid aneurysms. METHODS: Through an extradural pretemporal approach, the lateral wall of the CS is exposed. The dura between the trochlear nerve and V1 is opened, and access is made to the horizontal segment of the IC-ICA. After circumferential dissection, the temporary clip can be introduced to the artery, and the extradural clinoidectomy can be continued under secured proximal control. RESULTS: Seven patients with complex paraclinoid aneurysms were treated between May 2013 and May 2016 by the senior author. Temporary clipping of the IC-ICA was performed in all cases. Average time to achieve proximal control was 22.6 min (22.6 ± 13.8). One patient developed transient oculomotor palsy postoperatively. There were no other complications. CONCLUSION: When the exposed clinoidal segment of the internal carotid artery does not offer sufficient proximal space for temporary clipping, the extradural approach can be extended to the horizontal portion of the IC-ICA. In our experience, this technique is a quick, reliable, and safe alternative to the classical modalities of temporary occlusion.